DETERMINANT TAXPAYER COMPLIANCE IN PAYING HOTEL TAXES - Chandra, Teddy; Fransiska, Helen; Martha, Martha (Bilancia : Jurnal Ilmiah Akuntansi, 2024)
ABSTRACT The purpose of this research is to determine and analyze the effect of knowledge of taxation, tax sanctions and awareness of taxpayers on taxpayer compliance in paying hotel taxes. This research was conducted on Jl. Badak Ujung, Pekanbaru Mayor Office Complex, Main Building Lt. II - Tenayan Raya. The population in this research were hotel taxable entrepreneurs, totaling 148. With the census technique, the entire population was sampled in this research. This research technique uses multiple linear regression analysis. The results of the research explain that tax knowledge has a positive and significant effect, tax sanctions have a positive and significant effect and taxpayer awareness has a positive and significant on taxpayer compliance with hotel taxable entrepreneurs. Tujuan penelitian adalah untuk mengetahui dan menganalisis pengaruh pengetahuan perpajakan, sanksi pajak dan kesadaran wajib pajak terhadap kepatuhan wajib pajak membayar pajak hotel. Penelitian ini dilakukan di Jl. Badak Ujung, Komplek Perkantoran Walikota Pekanbaru, Gedung Utama Lt. II - Tenayan Raya. Populasi dalam penelitian ini adalah Pengusaha Kena Pajak Hotel yang berjumlah 148. Dengan teknik sensus maka keseluruhan populasi dijadikan sampel dalam penelitian ini. Teknik penelitian ini menggunakan analisis regresi linier berganda. Hasil penelitian menjelaskan bahwa pengetahuan perpajakan memiliki pengaruh positif dan signifikan, sanksi pajak berpengaruh positif dan signifikan dan kesadaran wajib pajak berpengaruh positif dan signifikan terhadap kepatuhan wajib pajak pengusaha kena pajak hotel.